Voice mail application for visually impaired persons - Hossain, Taslima Binte; Akter, Yeasmin Ara; Rahman, Md. Ataur (Recent Research in Science and Technology, 2020)
Technology-based applications are developed day by day in the whole world. But more of those are unusable for the visually impaired people. One of such applications, email has become an important and significant part of formal communication in the professional world. Thus, Voice Mail turns out to be an application through which visionless people can easily send or receive emails. The application uses “Voice to Text” and “Text to Voice” conversion to be usable for the visually impaired people. The system at first takes voice signals from the users as inputs, processes the signals and then converts that voice signals into the text. After that a text processing method is applied to convert the text into voice. Finally, the gmail server is used to connect the server with generating address to send or receive any mail. This application is useful for not only blind people but also for the normal people who always remain busy and doesn’t have time to type in keyboard. Moreover, this application is very much helpful and efficient in time utilization.